1869 Ky. Acts 481 - (:unkn) unknown (My University, 1869)
An Act to Amend and Reduce into One the Several Acts in Reference to the Town of Princeton, art. V, pt. 14: To regulate the keeping and conveying of gun-powder and other combustible and dangerous materials.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER